2004
DOI: 10.1074/jbc.m311737200
|View full text |Cite
|
Sign up to set email alerts
|

Marlin-1, a Novel RNA-binding Protein Associates with GABA Receptors

Abstract: GABA B receptors are heterodimeric G protein-coupled receptors that mediate slow synaptic inhibition in the central nervous system. Whereas heterodimerization between GABA B receptor GABA B R1 and GABA B R2 subunits is essential for functional expression, how neurons coordinate the assembly of these critical receptors remains to be established. Here we have identified Marlin-1, a novel GABA B receptor-binding protein that associates specifically with the GABA B R1 subunit in yeast, tissue culture cells, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 51 publications
(47 reference statements)
3
79
0
1
Order By: Relevance
“…Neuronal transfection. Dissociated E18 hippocampal neurons were transfected by nucleofection according to the protocol of the manufacturer (Amaxa, Cologne, Germany) with 3 g of single subunit plasmid DNA, plated and maintained in culture for 18 -21 d (Couve et al, 2004;Kittler et al, 2004;Jacob et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal transfection. Dissociated E18 hippocampal neurons were transfected by nucleofection according to the protocol of the manufacturer (Amaxa, Cologne, Germany) with 3 g of single subunit plasmid DNA, plated and maintained in culture for 18 -21 d (Couve et al, 2004;Kittler et al, 2004;Jacob et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures of cortical and hippocampal neurons were prepared as described (8,(17)(18)(19)(20). Nucleofection of cortical and hippocampal neurons (19) was carried out following the manufacturer's protocol (Amaxa, Gaithersburg, MD). Immunolocalization studies were carried out as described (8,17), using guinea pig ␣-GABA A R ␥2 subunit at 1:100 and ␣-HAP1 (1:100).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we previously reported that association of GABA B receptors with the GABA A receptor ␥2S subunit confers agonist-mediated endocytosis on GABA B receptors expressed in heterologous cells (16). Furthermore, GABA B receptors have also been shown to be regulated by interactions with several other protein partners, including the transcription factors cAMP-response element-binding protein 2 and ATF4 (17,18), the adaptor protein 14-3-3 (19), the RNAbinding protein Marlin-1 (20), and the coat protein I (21).…”
Section: Gaba Bmentioning
confidence: 99%